Risk Mitigation Strategy Using House of Risk and Root Cause Analysis for Hammer Mill Failure: Strategi Mitigasi Risiko Menggunakan Model Rumah Risiko dan Analisis Penyebab Utama untuk Gagal Mesin Penggiling Palu - Riyadi, Attila Daffa; Rusindiyanto, Rusindiyanto (Universitas Muhammadiyah Sidoarjo, 2025)
Background: In the animal feed manufacturing industry, machine reliability is essential for uninterrupted operations. Specific Background: PT XYZ, a poultry feed producer, experiences production inefficiencies due to frequent Hammer Mill failures. Knowledge Gap: Despite the critical role of machine reliability, limited studies address risk prioritization and mitigation strategies using integrative methods in this context. Aim: This study aims to identify and mitigate the dominant risk factors contributing to Hammer Mill failures through a structured risk management approach. Results: Using the House of Risk (HOR) Phase 1, five major risk agents were identified based on their Aggregate Risk Potential (ARP): lack of routine maintenance (ARP 1496), overused components (ARP 1080), foreign particle contamination (ARP 861), voltage fluctuations (ARP 510), and machine overload (ARP 432). Root Cause Analysis (RCA) traced the origin of these risks, and HOR Phase 2 prioritized mitigation actions using the Effectiveness to Difficulty Ratio (ETD). Novelty: The study integrates HOR and RCA to offer a quantitative and root-focused risk management framework. Implications: The proposed preventive maintenance scheduling system, identified as the most effective mitigation strategy, provides a replicable model for reducing downtime and enhancing production efficiency in industrial settings. Highlights: Identifies key risk factors causing machine failure. Combines HOR and RCA for effective mitigation. Proposes a preventive maintenance system to reduce downtime. Keywords: Hammer Mill, Risk Management, Root Cause Analysis, House of Risk, Preventive Maintenance